Coping in High-Risk Snow-Sports: A Qualitative Exploration of Alpine Racing and Freestyle Athletes' Experiences. Issue 4 (19th May 2017) - Kiemle-Gabbay, Laura; Lavallee, David
ABSTRACT: This study examines how semi-elite student snow-sport athletes utilize process and trait coping strategies to combat risk-taking, potential loss and trauma, and other stressors integral to their sport participation. Factors influencing coping strategy preference are also explored. Semistructured interviews were used to explore 10 participants' experiences; the narratives were analyzed using thematic analysis. Five master themes emerged from the analysis: Challenges to Overcome; Taking Action; Changing Perspectives; Staying in Control; and Underlying Influences. The findings highlight how participants develop and utilize preferred coping strategies, although the unpredictable nature of snow-sports can result in situation-specific process coping. Findings are discussed in relation to the differences between racing and freestyle disciplines.